THE CORRELATION BETWEEN FOOD SKILLS AND HEALTHY FOOD PREFERENCES AMONG MIDDLE-AGED ADULTS IN CROSS RIVER STATE, NIGERIA (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
This study explores the correlation between food skills and healthy food preferences among middle-aged adults (aged 40–60) in Cross River State, Nigeria, a region undergoing rapid nutrition transition. Using a cross-sectional design, data were collected from 500 participants across urban and rural communities via structured questionnaires and semi-structured interviews. Findings reveal a significant positive correlation (r = 0.62, p < 0.01) between food skills encompassing meal planning, preparation, and budgeting and preferences for nutrient-dense foods like fruits, vegetables, and whole grains. Socio-demographic factors, including education (β = 0.28, p < 0.05) and income (β = 0.19, p < 0.05), significantly influenced this relationship, with urban residents showing stronger preferences for processed foods. Rural participants with higher food skills demonstrated greater adherence to traditional, healthier diets (p < 0.01). The socio-ecological model guided the study, highlighting the interplay of individual, interpersonal, and environmental factors in shaping food choices. These findings underscore the need for targeted interventions to enhance food skills, particularly in urban areas, to promote healthier dietary patterns and combat the rising burden of non-communicable diseases (NCDs). Recommendations include community-based cooking programs and nutrition education tailored to local contexts. This study contributes to understanding dietary behaviors in Nigeria’s nutrition transition landscape.